Observation of Confinement‐Induced Self‐Poling Effects in Ferroelectric Polymer Nanowires Grown by Template Wetting. Issue 9 (14th July 2016) - Whiter, Richard A.; Calahorra, Yonatan; Ou, Canlin; Kar‐Narayan, Sohini
Abstract : "Self‐poled" polyvinylidene fluoride‐trifluoroethylene nanowires fabricated by solution wetting of nanoporous templates are measured with differential scanning calorimetry, Fourier transform IR spectroscopy, and dielectric permittivity measurements. These are quantitatively compared with measurements taken on electrically poled spin‐coated films before and after subsequent depoling heat treatment to observe trends and determine the extent and nature of the self‐poling effect in the nanowires as induced by the confined growth process. Abstract : Ferroelectric polymer nanowires grown using a template‐wetting method are shown to achieve an orientated "self‐poled" structure resulting from the confined growth process. Self‐poling is highly desirable as it negates the need for high electric fields, mechanical stretching, and/or high temperatures typically associated with poling treatments in ferroelectric polymers, as required for piezoelectric and/or pyroelectric applications. Here, differential scanning calorimetry, infrared spectroscopy, and dielectric permittivity measurements have been presented on as‐fabricated template‐grown polyvinylidene fluoride‐trifluoroethylene nanowires, and quantitatively compared with spin‐cast films of the same composition that have been electrically poled, both before and after subsequent depoling temperature treatment. The measurements reveal remarkably similar trends between the physical properties of the as‐grown nanowires and the electrically poled film samples, providing insight into the material structure of the "self‐poled" nanowires. In addition, piezoresponse force microscopy data are presented that allow for unambiguous identification of self‐poling in ferroelectric polymer nanostructures. Our results indicate the suitability of the template‐wetting approach in fabricating nanowires that can be used directly for piezoelectric/pyroelectric applications, without the need for post‐deposition poling/processing.